SOSIALISASI SEJARAH INDONESIA KEPADA SISWA-SISWI SEKOLAH DASAR DI PESISIR SELATAN UNTUK MENINGKATKAN PEMAHAMAN MEREKA TENTANG PERKEMBANGAN BANGSA INDONESIA - Ferdinal Ferdinal; Yogi Kembara; Nopriyasman Nopriyasman; Oktavianus Oktavianus (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The socialization of Indonesian history to the students of the elementary schools in Pesisir Selatan Regency was aimed at providing an introduction to the country's history to such students, from the period of colonization to the time of Indonesian independence. The activity's implementation method includes modeling stories, quizzes, and posters through an ethical and aesthetic approach. The target of this activity was the students of Elementary School 39 Pasar Gompong and those of Elementary School 18 Tebing Tinggi, Nagari Kambang Barat, Lengayang, Pesisir Selatan, Sumatra Barat. This introduction to the history of Indonesia is essential, considering that elementary school students are generations of successors who should know their people's history. The implementation consists of three phases: preparation, implementation, and evaluation. The phase one was an approach to the partner school. The phase two was implementing activities in both schools by presenting Indonesian history material in classes 4 and 6. The last phase was an evaluation which was conducted along the socialization. Through the activities, the students were enthusiastic about taking part in historical introduction activities, starting with introduction implementation and ending with evaluation. The results of this activity showed that the students were able to understand the development of Indonesian nation through Indonesia's history, especially the struggle of Indonesian national heroes.